Perlindungan Hukum Pidana Terhadap Istri Korban Kekerasan Ekonomi Dalam Rumah Tangga Oleh Suami - Pare, Prisko Yanuarius Djawaria; Waghi, Severinus; Taguwel, Maria Tfifonia; Duya, Maria Irene; Zae, Marsela Gaudensia; Ngasi, Maria Oktaviana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This research is descriptive qualitative research which is studied theoretically using a legal regulation approach and case studies that often occur in people's lives. The aim of this research is to reveal the facts of cases of domestic violence, specifically economic violence or commonly referred to as household violence, where the subject of the perpetrator is the husband and the victims are the wife and children. The research was carried out by conducting a theoretical study of laws and regulations that can ensnare victims of violence and protect victims of violence, as well as studying case studies with polemics that occur in people's lives. Efforts to prevent and overcome violence in society appear to be increasing. Among other things, violence against women has historically been known, but this incident has not been placed as a Social Legal Problem. If an act of violence occurs within the household, it is always resolved criminally using the Criminal Code. Examined from a normative perspective, the enactment of Law Number 23 of 2004 concerning the elimination of domestic violence provides a legal umbrella for victims of domestic violence. There are several arguments why women who are victims of domestic violence need legal protection (human rights protection or) providing compensation (restitution, compensation, social welfare guarantees/compensation). The key to this research is what form of criminal law protection takes place with the enforcement of applicable normative laws. against victims of economic violence (wives) committed by husbands. What is the function of witness and victim protection institutions in efforts to prevent and protect the rights of victims of domestic economic violence? Of course, it will be discussed in this article so that it provides readers with an overview so that they know the ins and outs of criminal acts of domestic economic violence